2010
DOI: 10.2353/jmoldx.2010.090115
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Oligonucleotide Array Comparative Genomic Hybridization for Etiological Diagnosis of Mental Retardation

Abstract: To assess the clinical utility of genome-wide oligonucleotide arrays in diagnosis of mental retardation and to address issues relating to interpretation of copy number changes (CNCs), we collected results on a total of 1499 proband patients from five academic diagnostic laboratories where the same 44K array platform has been used. Three of the five laboratories achieved a diagnostic yield of 14% and the other two had a yield of 11 and 7%, respectively. Approximately 80% of the abnormal cases had a single segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 29 publications
6
35
1
3
Order By: Relevance
“…These results are consistent with a previously published report [19]. Moreover, when Xiang et al [20] studied chromosomal aberrations associated with mental retardation, most of the confirmed pathogenic CNVs were >500 kb in size. In the present study, CNVs >500 kb were more likely to be pathogenic compared with the CNVs that were <500 kb [n = 6/49 (12.2%) vs. n = 1/74 (1.4%); p < 0.05].…”
Section: Resultssupporting
confidence: 82%
“…These results are consistent with a previously published report [19]. Moreover, when Xiang et al [20] studied chromosomal aberrations associated with mental retardation, most of the confirmed pathogenic CNVs were >500 kb in size. In the present study, CNVs >500 kb were more likely to be pathogenic compared with the CNVs that were <500 kb [n = 6/49 (12.2%) vs. n = 1/74 (1.4%); p < 0.05].…”
Section: Resultssupporting
confidence: 82%
“…A recent multi-center study on diagnostic aCGH application indicated that 12% of pediatric patients with intellectual disability (ID) and developmental delay (DD) are resulting from chromosomal and genomic imbalances [Xiang et al, 2010]. The recognition of increasing number of pathogenic genomic imbalances facilitates the mapping of dosage-sensitive genes and the understanding of mutagenesis mechanisms [Stankiewicz and Lupski, 2002;Vissers et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Recent diagnostic application of array comparative genomic hybridization (aCGH) for patients with development disorders showed enhanced analytical resolution and improved the abnormality detection rate [Xiang et al, 2008[Xiang et al, , 2010. Increasing number of genomic syndromes resulting from recurrent microdeletions and microduplications mediated by segmental duplicons or low copy repeats have been recognized [Stankiewicz and Lupski, 2002;Vissers et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…McMullan et al, 2009;Xiang et al, 2010;Tucker et al, 2011]. Whereas more than 95% of 'benign' CNVs that occur in healthy subjects have a size !…”
Section: Idiopathic Mental Retardation With or Without Congenital Abnmentioning
confidence: 99%